2007
DOI: 10.1002/chem.200700317
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically Initiated Single Polymer Immobilization

Abstract: This Concept article surveys methods for attaching single polymer molecules on solid substrates. A general approach to single polymer immobilization based on the photochemistry of perfluorophenylazides is elaborated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…Quantum chemical calculations on aryl azide compounds by the same authors showed that upon irradiation, in the excited state, the N-N 2 bond strength is weakened which causes the elimination of the nitrogen from azide groups to form nitrene. In yet another report by Yan [25], it was shown that in perfluorophenyl azides, the fluorine substituents increase the lifetime of the singlet nitrenes and thus the pathway for covalent adduct formation is favored and insertion reaction yields are greatly enhanced. Thus previous reports on photochemical nitrene insertion [24][25][26][27] demonstrate that use of aryl nitrenes to produce secondary amines (as in FNAB with PEDOT here) is a direct and a convenient process, with large yields, as the only pre-requisite, the polymer must fulfill is the presence of unencumbered -CH groups, which PEDOT easily satisfies.…”
Section: Morphology and Surface Roughnessmentioning
confidence: 98%
“…Quantum chemical calculations on aryl azide compounds by the same authors showed that upon irradiation, in the excited state, the N-N 2 bond strength is weakened which causes the elimination of the nitrogen from azide groups to form nitrene. In yet another report by Yan [25], it was shown that in perfluorophenyl azides, the fluorine substituents increase the lifetime of the singlet nitrenes and thus the pathway for covalent adduct formation is favored and insertion reaction yields are greatly enhanced. Thus previous reports on photochemical nitrene insertion [24][25][26][27] demonstrate that use of aryl nitrenes to produce secondary amines (as in FNAB with PEDOT here) is a direct and a convenient process, with large yields, as the only pre-requisite, the polymer must fulfill is the presence of unencumbered -CH groups, which PEDOT easily satisfies.…”
Section: Morphology and Surface Roughnessmentioning
confidence: 98%
“…We have developed a photochemically initiated coupling chemistry that employs functionalized perfluorophenyl azides (PFPAs) to attach molecules and materials to solid substrate surfaces (8688). Upon light activation, the azide moiety converts to a highly reactive nitrene that, notably, inserts into CH and NH bonds, creating highly robust covalent linkages.…”
Section: Photoinitiated Coupling Chemistrymentioning
confidence: 99%
“…This PFPA photochemical method has indeed been popular for surface modification and introducing functional groups into fullerenes, proteins, polymers, as well as carbohydrates. 20 Following this approach, mannose and galactose immobilization on glass surfaces was achieved using PFPA-modified carbohydrates. Due to the high reactivity of PFPAs under UV irradiation, the surface modification chemistry described in this study is an effective alternative to other surface functionalization strategies (Figure 1).…”
mentioning
confidence: 99%